2007
DOI: 10.1007/s00018-007-7352-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct activities of novel neurotoxins from Australian venomous snakes for nicotinic acetylcholine receptors

Abstract: Envenomation from Australian elapid snakes results in a myriad of neurological effects due to post-synaptic neurotoxins that bind and inhibit nicotinic acetylcholine receptors (nAChRs) of neurons and muscle fibres. However, despite the significant physiological effects of these toxins, they have remained largely undercharacterised at the molecular level. This study describes the identification and comparative analysis of multiple neurotoxin isoforms from ten Australian snakes, including functional characterisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
1
16
0
4
Order By: Relevance
“…Named ohanin, it became the first snake venom vespryn. Additional vespryns have subsequently been sequenced from various elapids [239] and crotalids [2,10,240,241], and from the viperid, Echis coloratus [242]. Crotalid vespryns are 28–32 residues longer at their N-termini than the elapid toxins.…”
Section: Resultsmentioning
confidence: 99%
“…Named ohanin, it became the first snake venom vespryn. Additional vespryns have subsequently been sequenced from various elapids [239] and crotalids [2,10,240,241], and from the viperid, Echis coloratus [242]. Crotalid vespryns are 28–32 residues longer at their N-termini than the elapid toxins.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-bacterial effects of omwaprin-b were further examined using the gram positive bacterial strains Staphylococcus aureus, Staphylococcus epidermis and Streptococcus epidermis in addition to the gram negative strains Escherichia coli and Pseudomonas aeruginosa according to the protocols described by Nair et al [17]. Potential neurotoxic effects of omwaprin-b were also examined via an ex vivo amphibian electrophysiological assay, testing inhibitory effects on end-plate potentials (EPPs) and minature EPPs at the toad neuromuscular-junction as previously described [29].…”
Section: Methodsmentioning
confidence: 99%
“…The molecular accelerated evolution, classification and nomenclature of these toxins are subject to debate Sunagar et al, 2013). Although a huge diversity of genes and transcripts have been described (Gong et al, 1999;Jackson et al, 2013;St Pierre et al, 2007b;Tyler et al, 1987), the usual simplified short-chain neurotoxin (SNTx) or long-chain neurotoxin (LNTx) classification is used here (Hegde et al, 2009).…”
Section: Three-finger Toxinsmentioning
confidence: 99%
“…The previously described "LNTx-1" (St Pierre et al, 2007b) and an isoform were identified in isogroup 23. The isogroup 83 encodes for "Pseudonajatoxin b homologue" (Gong et al, 2001) and isotig 1328 is a new LNTx transcript, named here "LNTx-2", with 93% translation similarity to a Pseudonaja modesta LNTx (Accession: R4G319_9SAUR) , 85% to a-neurotoxin "LNTx 20" from Drysdalia coronoides (Accession: 3FL20_DRYCN) (Chatrath et al, 2011) and only 78% similar to "Pseudonajatoxin b homologue".…”
Section: Three-finger Toxinsmentioning
confidence: 99%
See 1 more Smart Citation